Distribution of Expiation for Non-Muslims: Analysis of the Ta'lili Method of Reasoning Regarding the Case of Kaffarat - Ikbal, Muhammad; Abdullah, Abdullah; Zulhamdi, Zulhamdi (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2025)
Mujtahids do not create, but only discover laws. This is because of the Islamic belief that laws are created by God as the lawmaker (al-Shari'). Humans/mujtahids only understand (fiqh) the divine law. The process of understanding the law is called istinbaht al-hukm through an intellectual activity called ijtihad. The legal results obtained through istinbath ijtihad are called fiqh. The purpose of discovering the law must be understood by mujtahids in order to develop legal thought in Islam in general and address contemporary legal issues whose cases are not explicitly regulated by the Quran and Hadith. Therefore, by applying various methods, it is hoped that laws can be found to solve various problems that arise. This journal will attempt to describe the ta'lili method of discovering law. Based on a study of the concepts of ta'lili reasoning regarding the distribution of kaffarat oaths to non-Muslims, conclusions can be drawn, namely: First, the obligation to pay kaffarat oaths as contained in the Al-Qur'an surah al-Maidah verse 89, is mukhayyar, namely freeing slaves, providing food or clothing, if you are unable to carry out these three things, you are obliged to fast for three days. Second, Abu Hanifah r.a. does not require a believing slave to be the target of an oath of infidelity. Abu Hanifah r.a. does not turn the word muthlaq away from muqayyad, he gives charity to the common word (muthlaq). Third, it is permissible to free ahl al-dzimmah (non-Muslim) slaves as sworn inmates and also provide food or clothing to ahl al-dzimmah (non-Muslims). Because of the statement on the issue of distributing kafarat oaths, there is no specific text that recommends giving them to believers. Fourth, giving kafarat oaths to ahl al-dzimmah (non-Muslims) in terms of maqâshid syariyyah is almost the same as giving zakat to converts, namely to persuade their hearts to Islam.